1986
DOI: 10.1002/lary.1986.96.11.1243
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Tonsillectomy Hemorrhage: Incidence, Prevention and Management

Abstract: Tonsillectomy (with or without adenoidectomy) continues to be a commonly performed operation in the United States. Over the years, the incidence of post‐tonsillectomy hemorrhage (reported between 0% and 20%) has decreased, but continues to pose serious problems. We reviewed 1,445 tonsillectomies performed over a 2‐year period to study the incidence of post‐tonsillectomy hemorrhage. Thirty‐eight of 1,445 children (2.62%) had postoperative bleeding. The incidence of primary hemorrhage (within 24 hours) was 0.14%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
2
10

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(127 citation statements)
references
References 17 publications
6
109
2
10
Order By: Relevance
“…We observed a 14% incidence of excessive bleeding in the kctorolac group, which is greater than the expected rate of less than 3%. 15 The unexpected bleeding appeared to be an individual response; that is, if we excluded the patients with marked bleeding from analysis, the bleeding was almost identical in groups. When we began our study, there were no reports of ketorolac being associated with important perioperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a 14% incidence of excessive bleeding in the kctorolac group, which is greater than the expected rate of less than 3%. 15 The unexpected bleeding appeared to be an individual response; that is, if we excluded the patients with marked bleeding from analysis, the bleeding was almost identical in groups. When we began our study, there were no reports of ketorolac being associated with important perioperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…2'3 Infection following tonsillectomy is uncommon, 4 and nasopharyngeal stenosis, atlantoaxial subluxation, meningitis, depression, and death are extremely rare. [5][6][7] Postoperative pain can be treated with systemic analgesic therapy in combination with local infiltration of anesthetics or local application of analgesics, although some investigators have been unable to show the effect of locally applied therapy. 8-11 Nonsteroidal anti-inflammatory drugs (NSAIDs) are used for pain relief following tonsillectomy 12 and may also reduce postoperative nausea and vomiting.…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al [6] found that 89 of 90 bleeds were secondary in 4,662 patients. The causes of secondary bleeding are residual tonsillar tissue, infection, an incorrect diet such as an acidic liquid or solid food, trauma, and the use of nonsteroidal anti-inflammatory drugs [7,8]. However, we attribute the bleeding in our patients to extremely hot environments.…”
Section: Summermentioning
confidence: 84%
“…Tonsillectomy is frequently performed in otorhinolaryngological clinics, and is associated with possible bleeding, aspiration, laryngospasm, and circulatory collapse [4,8]. Primary bleeding is thought to be associated with the surgical technique employed.…”
Section: Discussionmentioning
confidence: 99%